Generalized Multiprotocol Label Switching convergence NETWORKS IN THE SCHEME - Eriek Eriek Orlando (JAKSTIK Journal, 2004)
Convergence of Internet and telecommunications, with applications in it are more and morebandwidth with QoS penqaturan it finally takes the network and the elements in it which gavefull support to the preservation and improvement of network performance. If the bandwidth isalways the first object is predicted, then the current scheme requires some applications have"bandwidth on demand". On the other hand the network efficiency by leveraging publicnetworks to be the main constraint in the deployment of services, especially for commercialpurposes. Trasnport technology which is required not only discovery allows routing and bestpath, but can also accommodate non-package existing technologies. The author describes thedevelopment of GMPLS today, particularly in the scheme of network convergence with othertransport technologies. Also described briefly about the relationship pengembanngannyaMPLS as the base.Keyword: MPLS, GMPLS, QoS, Bandwidth